Perception and Lexicon Labeling Ability on a Child with Language Delay Diagnosed As Autistic Spectrum Disorder: A Psycholinguistic Study - Rohmani Nur Indah (Register Journal, 2011)
This research focuses on the semantics acquisition of a child with language delay diagnosed as autistic spectrum disorder (ASD). The research problem is on how the child acquired the ability to comprehend meaning. It aims at answering the questions on how the child identified lexical meanings and how he labeled targeted lexicons of his first language. The approach employed in this research is descriptive qualitative to get adequate explanation on a specific language phenomenon, namely semantics acquisition. Its design is case study with the type neo-ethnographic. As the data collection method, it uses participant observation of longitudinal study considering that the research subject has familial relation with the researcher. The data analysis shows that the semantic acquisition of the research subject has complexity in vocabulary enrichment. The research subject often performs echolalic speech when he is asked to identify or label certain object given. The typical idiosyncratic speech is shown by the unique feature of limited syllable and prosody. In general, his ability to identify lexical meanings is far exceeding his ability to label objects. He also has sensitivity to perceive the non-verbal symbol performed by the people he knows well. The use of verbal language supported by non-verbal language facilitates his perception. He finds it difficult to comprehend the lexicons having similar sound as he assumes that one lexicon represents one object which typically belongs to concrete object. In addition, the ability of the research subject in labeling objects cannot be developed easily because of his difficulty in expressing ideas through words. To pronounce the words correctly, he shows high anxiety by lowering down his speech. In selecting the lexicon he also finds it hard to use pronoun, to label homonyms and to apply both polysemy and hyponym. Accordingly, he tends to communicate only to fulfill his needs by asking things, asking the listeners to do or not to do something, and protesting something as shown in the contexts. Further, he is likely to label objects by the lexicons got from the immediate exposure.keywords; Autistic Spectrum Disorder (ASD);  Language Acquisition;  Psycholinguistics